A Competitive Partnership Formation Process - Tommy Andersson; Jens Gudmundsson; Adolphus Talman; Zaifu Yang (Lund University, School of Economics and Management, Department of Economics, 2013)
A group of heterogeneous agents may form partnerships in pairs. All single agents as well as all partnerships generate values. If two agents choose to cooperate, they need to specify how to split their joint value among one another. In equilibrium, which may or may not exist, no agents have incentives to break up or form new partnerships. This paper proposes a dynamic competitive adjustment process that always either finds an equilibrium or exclusively disproves the existence of any equilibrium in finitely many steps. When an equilibrium exists, partnership and revenue distribution will be automatically and endogenously determined by the process. Moreover, several fundamental properties of the equilibrium solution and the model are derived.
Keywords: C62; C72; D02; 330; Partnership formation; adjustment process; equilibrium; assignment market